Penerapan Pembuatan Video Pembelajaran Bahasa Inggris dalam Meningkatkan Motivasi Belajar Siswa - Reynold P. J. Vigeleyn Nikijuluw; Sylvia Irene Persulessy; Juvrianto Chrissunday Jakob; Ahmad Nusi; Hindri Febri Ana Sari (Scholars, 2023)
Learning videos are interactive media that are currently commonly used in learning, especially in English subjects in recent times. Providing a positive impact on students' motivation in learning English is one of the benefits obtained from the application of this learning media. English learning videos made by involving students as actors in it are expected to foster their motivation in learning English. As for the purpose of this study, it was found that from the research data it was found that students were more motivated by learning English in class using the videos they participated in. Focusing on research methodology, descriptive quantitative research is applied to obtain research objectives. The results of the research obtained in this study are narrated in descriptive form.Keywords: learning videos, student motivation, English learning